2020
DOI: 10.1007/s42452-020-03720-z
|View full text |Cite|
|
Sign up to set email alerts
|

Use of lignocellulosic corn and rice wastes as substrates for oyster mushroom (Pleurotus ostreatus Jacq.) cultivation

Abstract: The accumulation of agronomic wastes has caused several environmental problems, such as air and soil contamination, and insect and pathogen proliferation, among others. To mitigate this, studies have evaluated the use of these wastes as substrates for the cultivation of Pleurotus mushrooms, a low-cost/nutritionally important crop. This study aimed to evaluate the use of corn stubble and rice straw as substrates for the in vitro production of oyster mushrooms (Pleurotus ostreatus Jacq.) and the productive chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
0
12
1
2
Order By: Relevance
“…In concurrence, the MLGR was significantly higher in T2 (culture media based on sorghum grains) in comparison with wheat and maize-based cultures (T1 and T3) (higher by 2.6 mm/day and 1.0 mm/day, respectively) (table 9). An earlier study found that the linear growth rate of P. ostreatus on wheat grains was around 3.5-4.0 mm/day at an inoculation temperature of 25°C [26] being lower by 40-46% lower than in the current study. An MGR of 31.5-38.6 mm was acknowledged after 8 days of inoculation on white and red sorghum grains [27] being much lower than in the current study (90 mm).…”
Section: 3contrasting
confidence: 79%
See 1 more Smart Citation
“…In concurrence, the MLGR was significantly higher in T2 (culture media based on sorghum grains) in comparison with wheat and maize-based cultures (T1 and T3) (higher by 2.6 mm/day and 1.0 mm/day, respectively) (table 9). An earlier study found that the linear growth rate of P. ostreatus on wheat grains was around 3.5-4.0 mm/day at an inoculation temperature of 25°C [26] being lower by 40-46% lower than in the current study. An MGR of 31.5-38.6 mm was acknowledged after 8 days of inoculation on white and red sorghum grains [27] being much lower than in the current study (90 mm).…”
Section: 3contrasting
confidence: 79%
“…This may point the role of tea extract when combined with olive leaves one in the hastening of mycelial growth. Green tea extract contains valuable enzymes [26] that may have been liberated and thus helped in the decomposition of holocellulose compounds (found in olive and tea extracts) and the provision of needed energy for P. ostreatus mycelium growth [9,10].…”
Section: (E) (D)mentioning
confidence: 99%
“…Many reports have discussed the many purposes of oyster mushrooms through their cultivation on agro-wastes or agro-industrial wastes, which include mushroom production, and the biodegradation of agro-wastes, producing many bioactive compounds and creating a healthy environment for humans, as well as these mushrooms possessing pharmaceutical attributes for medical applications, such as anti-diabetic, anti-carcinogenic, anti-oxidative, and immune suppressor attributes (e.g., [11,12,61,[112][113][114]. Furthermore, oyster mushrooms have a great ability to convert the agro-wastes into bioenergy, bio-compost and biofertilizers [60,115].…”
Section: Recycling Of Organic Solid Wastes By Pleurotus Ostreatusmentioning
confidence: 99%
“…Previous research showed an increase in mycelium run when two or more substrates were combined (Baysal et al, 2003;Mane et al, 2007;Owaid et al, 2016). The growth rate of mycelium is affected by substrate chemical composition, plant structure, origin, particle size, and the presence of polyphenols (Jonathan et al, 2012;Zárate-Salazar et al, 2020).…”
Section: Growth Of P Djamormentioning
confidence: 99%